Stigmatodon enigmaticus (Bromeliaceae, Tillandsioideae), a new lithophytic species from the Campos Rupestres within the Brazilian Atlantic Forest - Couto, Dayvid R.; Gonella, Paulo M.; Costa, Andrea F. (Phytotaxa, 2023)
Stigmatodon enigmaticus is described and illustrated as a new lithophytic taxon from the quartzitic Campos Rupestres within the biodiversity hotspot of the Atlantic Forest, in Minas Gerais state, Southeastern Brazil. This puzzling new species presents floral features that are unique in the genus as they are associated with ornithophily, as in most Vriesea, contrasting with the chiropterous features of all previously known Stigmatodon species. It is assigned to the “S. limae group”, being most similar to S. vexatus, with which it is compared. Stigmatodon enigmaticus is a microendemic species and is here assessed as Critically Endangered due to its restricted habitat, reduced population size, and threats from invasive species. This finding adds to several others that reinforce the relevance of the currently unprotected Serra do Padre Ângelo as a priority for conservation.